«Li sens conmence contreval a filer…». Imaginaire du sang et hétérodoxies épiques dans La Bataille Loquifer - Carlos F. Clamote Carreto (Medievalista)
Blood is, by nature, the vital and deadly substance which feeds the Chanson de Geste. Gathering a large range of symbolic and cultural strata, this polysemic fluid can either serve to embody the principle of continuity of the genealogical memory or to serve as the conveyor of the impure blood that runs through the veins of the cursed lineages of pagans or traitors. Tainted by the mark of ancestral taboos that shake the poetic discourse ( as with the vision of the blood that women shed, for example) or assigning the dangers of an open wound which threatens the integrity of the epic hero transformed into a sacrificial victim whose blood, shed on the battlefield, purifies and regenerates the space conquered by the Christian logos, blood creates and transmits a paradoxical imaginary which is both projected and reflected in the lineage and in the language, which reflects in the epic poetry itself. Hence the fact that in Old French, blood becomes an hypostasis of sens (meaning) by means of a marvelous homophony which seals as one the common fortune of both the substances and determines the particularly striking and unique poetics of blood which we can detect in the study and analysis of an atypical epic poem composed somewhere between the end of the 12th century and the beginnings of the 13th century, La Bataille Loquifer.